Japanese Herbal Medicine Ninjinyoeito Mediates Its Orexigenic Properties Partially by Activating Orexin 1 Receptors - Miyano, Kanako; Ohshima, Kaori; Suzuki, Nozomi; Furuya, Saho; Yoshida, Yuki; Nonaka, Miki; Higami, Yoshikazu; Yoshizawa, Kazumi; Fujii, Hideaki; Uezono, Yasuhito (Frontiers in Nutrition, 2020)
Cancer cachexia is highly prevalent in patients with progressive cancer and is characterized by decreased food consumption and body weight. Japanese herbal medicine Ninjinyoeito (NYT), composed of 12 herbal crude drugs, is prescribed in Asian countries to improve several symptoms such as anorexia and fatigue, which are commonly observed in patients with cancer cachexia. However, the action mechanisms of NYT in improving anorexia or fatigue in patients with cancer are not clear. Therefore, in the present study, we examined the effects of NYT on the activities of several G-protein-coupled receptors (GPCRs), which activate hyperphagia signaling in the central nervous system, using an in vitro assay with the CellKey™ system, which detects the activation of GPCRs as a change in intracellular impedance (ΔZ). NYT increased the ΔZ of human embryonic kidney 293 (HEK293) cells expressing orexin 1 receptor (OX1R) and those expressing neuropeptide Y1 receptor (NPY1R) in a dose-dependent manner. On the contrary, NYT did not significantly increase the ΔZ of HEK293A cells expressing growth hormone secretagogue receptor (GHSR) and those expressing NPY5R. The selective OX1R antagonist SB674042 significantly decreased the NYT-induced increase in ΔZ in OX1R-expressing cells. Contrarily, the selective NPY1R antagonist BIBO3340 failed to inhibit the NPY-induced increase in ΔZ in NPY1R-expressing cells. Additionally, we prepared modified NYT excluding each one of the 12 herbal crude drugs in NYT and investigated the effects on the activity of OX1R. Among the 12 modified NYT formulations, the one without citrus unshiu peel failed to activate OX1R. A screening of each of the 12 herbal crude drugs showed that citrus unshiu peel significantly activated OX1R, which was significantly suppressed by SB674042. These finding suggest that NYT and citrus unshiu peel could increase food intake via activation of orexigenic OX1R-expressing neurons in the hypothalamus. This study provides scientific evidence to support the potential of NYT for cancer patients with anorexia.